An Analysis Of Students’ Perception toward the Interactive E-Book Used in Advanced Grammar at English Department of Universitas Negeri Padang - Chikal Lexsti Rahmadani; Fitrawati Fitrawati (Universitas Negeri Padang, 2020)
The use of this kind of technology can be the big change in English classroom, especially in grammar class. With all the ability of the interactive e-book provided for students, their thoughts toward this e-book is needed since they are the direct users who mostly use it for learning. Thus, the aim of this study was to analyse students’ perception toward the use of interactive e-book used in grammar class, specifically in Advanced Grammar class. This research was descriptive research which was conducted at English Department, Universitas Negeri Padang. The sample of this research was the students who took advanced grammar class and use interactive e-book. The data was collected by using questionnaire which contained 4 aspect: interface, interactivity, content (teaching material and learning exercise), and practicality with 71 statements. Result indicated that students have positive perception toward the interactive e-book with the average mean score 3.15. The result suggests the consideration to improve the interactive e-book to create the e-book which is suitable for students.